Measurements of the solidification process of resins from cantilever beams resonances - Arenas, Gustavo Francisco (2013)
In this work, we introduce a technique to infer elastic and mechanical properties of light-curing resins by using cantilever beams. The methodology includes vibration resonance measurements performed with a fiber optic Fizeau interferometer. As is known, the natural resonance frequency of cantilever beams depends strongly on any variation in its physical properties and geometry. Following this idea, square shaped solid aluminum beams with a short transverse deep crack drilled near its fixed end were studied. The slot was filled with photo-curing resins and resonance frequency was monitored as polymerization proceeded. In order to track resonance peaks, we adopted a simple electromagnetic actuator to force the beam into oscillations of variable frequencies. Beams were scanned periodically around its natural resonance as photo-curing was carried out. Due to the small vibrations amplitude present at the free end of beams (tens of microns typically), we used a Fizeau interferometric fiber optic sensor placed near the free end. Its extremely high sensitivity and resolution are its outstanding features, yielding a non-invasive sensor that ensures natural evolution and distortionless amplitude and frequency measurements. Results show that liquid resin in the slot did not produce changes on beam resonance prior to curing. On the other hand, photo-polymerization partially recovered original properties of the beam in a few tens of seconds, suggesting that vitrification of resins is completely achieved while photoreaction is still occurring. Moreover, additional information of volumetric shrinkage of polymers can be extracted from these measurements. In summary, this powerful and simple technique enables to evaluate the static resonance of beams as well as polymer shrinkage and solidification time evolution in one single measurement.